2017
DOI: 10.1371/journal.pone.0189127
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic role of tumor size in early breast cancer in the era of molecular biology

Abstract: BackgroundThe prognosis of early breast cancer (EBC) depends on patient and tumor characteristics. The association between tumor size, the largest diameter in TNM staging, and prognosis is well recognized. According to TNM, tumors classified as T2, could have very different volumes; e.g. a tumor of 2.1 cm has a volume of 4500 mm3, while a tumor of 4.9 cm has a volume of 60.000 mm3 even belonging to the same class. The aim of the study is to establish if the prognostic role of tumor size, expressed as diameter … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
26
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 12 publications
5
26
0
2
Order By: Relevance
“…Our results, showing that both the number of positive ALNs and the presence of LVI have a negative impact on the survival rates, are in line with previously published data [32][33][34][35][36] . In concordance with former observations, BC molecular subtype also affected survival 12,24,31 .…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Our results, showing that both the number of positive ALNs and the presence of LVI have a negative impact on the survival rates, are in line with previously published data [32][33][34][35][36] . In concordance with former observations, BC molecular subtype also affected survival 12,24,31 .…”
Section: Discussionsupporting
confidence: 90%
“…The tumor size is established as an independent predictor of survival in BC patients 23 . However, its prognostic role has been denied in some papers 31 . In this study, tumor size, as well as higher histologic grades, were negatively correlated with the survival rates 8,13,14,18 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A high tumor/breast ratio (relatively large tumor and/ or small size breast) decreases BCS rate in patients with early stage breast cancer. Neo-adjuvant chemotherapy (NAC) to reduce tumor size, mastectomy with implant or simple mastectomy are the commonly selected options in these patients [29,30]. However, NAC has a limited effect on primary tumor and axilla especially in patients with luminal A molecular subtype [31].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a study by Yang et al, (2000) demonstrated significantly high expression levels of KAI-1 in normal breast tissues and benign breast tumours than in breast cancer. Breast cancer is typically categorised in stages based on American Joint Committee on Cancer (AJCC) TNM classification, (Tumor Nodes Metastasis) which recommends the tumor size (T), presence of metastatic lymph nodes (N) and metastasis (M) are the fundamental determinants of staging (Kasangian et al, 2017). Axillary lymph node status is one of the most vital prognostic factors and lymph node involvement is associated with high risk of distant metastasis, regional recurrence, and poor survival in breast carcinoma, where as patients with lymph node negative have favourable prognosis (Howland et al, 2013;Dings et al, 2013).…”
Section: Discussionmentioning
confidence: 99%